Intelligent Information Mode of College English Teaching Based on Multimedia Network Technology - Xuejing, Wu (International Journal of Information Studies, 2025)
The multimedia network technology has been developing rapidly in the past few years. Network resources should take an important role in college English teaching, of which the â€œstudents-centeredâ€ pattern should be promoted so that studentsâ€™ potential of studying independently can be developed. Despite efforts, some colleges and universities meet with difficulties in doing so. Overcoming these difficulties and structuring proper multimedia network ensure that multimedia network technology takes an important role in college English teaching.